Shonen note : boy soprano. 7 - Kamatani, Yuhki (Kodansha USA Publishing, LLC, 2024)
"After an unexpected mishap at the national choir competition, Midori loses sight of who she is and decides to resign from the choir. Meanwhile, Yutaka's time as a boy soprano is reaching its end as his voice begins to change. He hopes Midori will get to hear him perform one more time, but..."